Evaluation of multi-directional speed qualities throughout adolescence in youth soccer: The non-linear nature of transfer - Dugdale, J. H.; Myers, T.; Sanders, D.; Andrew, M.; Clarke, R.; Hunter, A. M. (Journal of Sports Sciences, 2024)
Training and assessment of agility is often prioritised by soccer coaches and practitioners aiming to develop multi-directional speed. Although the importance of agility is advocated throughout childhood and adolescence, limited data evidence agility performance at different stages of adolescence. The purpose of this study was to examine differences in multi-directional speed performance in youth soccer players spanning an entire soccer academy. A total of 86 male junior-elite soccer players volunteered to participate. Anthropometric data were collected, alongside performance data from a battery of physical tests including sprinting, jumping, change of direction, reaction time, and agility. Bayesian models using log-likelihoods from posterior simulations of parameter values displayed linear or curvilinear relationships between both chronological and biological age and performance in all tests other than agility and reaction time. For agility and reaction time tests, performance improved until ~14 years of age or the estimated age of peak height velocity whereby arrested development in performance was observed. Our results demonstrate that while most performance skills improve as chronological or biological age increases, measures of agility and reaction time may not. These findings support the notion that agility performance is complex and multifaceted, eliciting unique, challenging physical demands and non-linear development.